The Buddhism and policy in the history of Tuva - Otroshenko, Ivanna V. (The New Research of Tuva, 2014)
Article is devoted to the plans of the Russian politicians on creation in Tuva of a uniform spiritual management of Buddhists and election of its leader (1910’s). The active policy of Mongolia directed on returning of Tuva into its orbit of the influence became motive for modernization of Tuvan Sangha during the War and the Revolution. Russian politicians exploited the experience of construction of Northern-Buddhist hierarchy in the Russian Empire and hoped to reduce influence of the Mongolian hierarchs in Tuva.